Exploring free pregnancy associated plasma protein a (fPAPP-A) as a biomarker in early pregnancy - Petersen, Jesper Friis; Tiittanen, Vilma; Wittfooth, Saara; Løkkegaard, Ellen; Friis-Hansen, Lennart Jan (Elsevier BV, 2025)
Objectives: In combined first trimester screening for Down syndrome, Pregnancy-Associated Plasma Protein A (PAPP-A) is pivotal. PAPP-A tests evaluate total PAPP-A, consisting of the biologically active free PAPP-A (fPAPP-A) and PAPP-A complexed with eosinophil major basic protein's proform (proMBP). While PAPP-A is well-researched, limited understanding persists regarding fPAPP-A's first trimester concentrations and diagnostic utility.
Design and methods: PAPP-A and fPAPP-A levels were gauged in 602 serum samples at 2-week intervals (gestational weeks 4–14) from 159 women with delivery of a healthy neonate and 80 samples from 37 miscarriages. The final sample at the time of diagnosis from women who miscarried was included in analyses.
Results: During the first trimester, PAPP-A and fPAPP-A levels displayed significant and strong correlation (r = 0.94), with median values doubling weekly. Free PAPP-A constituted only 3.0 % of PAPP-A over gestational weeks. Low fPAPP-A linked to miscarriage (p < 0.001), maternal weight (p < 0.001), and smoking (p = 0.02). For miscarriage prediction fPAPP-A was equal to PAPP-A (area under the receiver operating characteristics curve 0.79 vs. 0.81, p = 0.44).
Conclusions: Investigating fPAPP-A presence and concentration directly in first trimester serum has not been done previously. This study report lower fPAPP-A values than anticipated from prior enzymatic studies of fPAPP-A. fPAPP-A was not superior to PAPP-A as a first trimester biomarker in this dataset.